9,10-Dioxoanthracene-1,4-diyl bis(4-methylbenzenesulfonate) - Teerawatananond, Thapong (International Union of Crystallography, 2012)
The title molecule, C(28)H(20)O(8)S(2), has a T-shaped conformation. The central 9,10-anthraquinone moiety is bow-shaped with the two outer aromatic rings being inclined to one another by 13.99 (11)°. The benzenesulfonate rings are inclined to one another by 47.35 (12)°, and by 34.51 (11) and 17.88 (11)° to the bridging aromatic ring of the 9,10-anthraquinone moiety. In the crystal, C—H⋯O interactions link the molecules into ribbons in [100].